LAYANAN BIMBINGAN DAN KONSELING PADA LEMBAGA PENDIDIKAN ANAK USIA DINI - Muhamad Rifa’i Subhi; Asrul Faruq (QURROTI, 2021)
This study aims to obtain several alternative forms of guidance and counseling services at early childhood education institutions. This research uses library research method. Problems and data collection originate from literature review as a scientific presentation carried out by selecting literature related to the research theme. Sources of data used come from literature that discusses various forms or models of guidance and counseling services in early childhood education institutions. The analysis technique uses the content analysis method. The results showed that among the forms of guidance and counseling services that can be applied to early childhood education institutions are guidance and counseling services using the child-centered play therapy (CCPT) approach, person-centered consultation; and solution-focused brief therapy (SFBT). Guidance and counseling service practices at early childhood education institutions can run optimally if you pay attention to several key words that discuss the abilities of counselors, counselor partners, and the characteristics of early childhood.